Pengaruh Koefisien Respon Laba terhadap Financial Leverage dan Risiko Sistematis (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Amas Augustian Harahap (Program Magister Akuntansi Unsyiah, 2016)
The purpose of this research is to examine and analyze the influence of financial leverage and systematic risk towards earning response coefficients on listed manufacturing companies at the Indonesia Stock Exchange in 2009, 2010, and 2011. The research type used was verificative reaserch by using census method. The target population of this research were listed manufacturing companies at the Indonesia Stock Exchange which have positive unexpected earnings and positive earnings for three years. After being selected, the target population for 2009-2011 were 13 emitens. Thetotal research population were 39 observation (13 emitens for three years observation). The data used in this research were secondary data, which were obtained from audited financial reporting for the book year ended December 31, 2009, 2010, and 2011 and also stock price and composite stock price index data during the observation period which published by the stock market reference center at the Indonesia Stock Exchange. The results of this research showed that financial leverage and systematic risk simultaneously influence to earning response coefficients. Partially financial leverage had positive influence to earning response coefficients and systematic risk has negative influence to earning response coefficients.KEYWORDS : Earning response coefficients, financial leverage, and systematic risk